Pengembangan E-Modul Berbasis Aplikasi Flipbook Pada Mata Kuliah Sistem Operasi Kepelabuhanan Untuk Meningkatkan Literasi Mahasiswa Prodi Transportasi Laut - Retian Asfirah, Lia; Anggoro, Retno; M, Masriah; A, Alimatussa'diyah; Dwi Retnandari, Septina; Shintawati Setyaningrum, Dewi (Information Technology Education Department, 2024)
In the era of industrial revolution 4.0 and towards 5.0, digital learning media is a practical choice to improve student education. The use of digital flipbook learning media at Politeknik Maritim Negeri Indonesia, especially in the Marine Transportation study program, is an ingenious strategy to create a more dynamic, communicative and participatory learning environment. The current Port Operations System course module is still in conventional form, not in accordance with the latest literacy. This research aims to provide learning resources and electronic modules using the Flipbook application to update materials and facilitate students in learning activities. The ADDIE paradigm is used in analysis, design, development, implementation, and evaluation. Evaluation is conducted in the analysis process to ensure conformity with the curriculum. The design process involves systematic module design and integration of current reading standards. E-Modules linked to the Canva application added visual and interactive elements. Implementation is done by integrating the module content into a flipbook application, ensuring students can easily access teaching resources for the Port Operating System course.